1992
DOI: 10.1002/jcp.1041530303
|View full text |Cite
|
Sign up to set email alerts
|

Similar, but not identical, modulation of expression of extracellular matrix components during in vitro and in vivo aging of human skin fibroblasts

Abstract: Regulation of the synthesis of procollagen and other extracellular matrix components was examined in human skin fibroblasts obtained from donors of various ages, from fetal to 80 years old (in vivo aged), and in fetal fibroblasts at varying passage levels (in vitro aged). Growth rates and saturation densities of fibroblasts decreased with increasing age of the donor and after passage 20 of fetal fibroblasts. The rates of collagen and proteoglycan synthesis also decreased during both types of aging to about 10-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
49
1
3

Year Published

1995
1995
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 45 publications
10
49
1
3
Order By: Relevance
“…Previous studies have demonstrated that age-related modifications are related to cell division, DNA synthesis and cell migration changed by mechanical forces (33,42,43). It has been reported that fibroblast aging is associated with the disruption of cytoskeletal function, such as decreased actin polymerization, which in turn reduces cell elasticity (36,44).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that age-related modifications are related to cell division, DNA synthesis and cell migration changed by mechanical forces (33,42,43). It has been reported that fibroblast aging is associated with the disruption of cytoskeletal function, such as decreased actin polymerization, which in turn reduces cell elasticity (36,44).…”
Section: Discussionmentioning
confidence: 99%
“…Other sources of cells used in bone tissue engineering include adiposederived stem cells [32] and periosteal cells [40,65]. Human dermal fibroblasts are another attractive source of cells that can meet the criteria for bone tissue engineering [89]. Recent studies have investigated the ability of cells committed to a fibroblastic lineage to undergo osteogenic differentiation.…”
Section: Design Considerations For Functional Tissue Engineering Of Pmentioning
confidence: 99%
“…To date, several studies have examined age-related alterations in cell division, biosynthesis (1)(2)(3), and cell migration (4), but there is little information about the relationship between aging and the mechanical properties of cells. Previous studies have shown that biomechanical properties are important for cell functions that are regulated by mechanical forces (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Changes in mechanical properties of the skin are generally referred to extracellular aspects such as alterations in polymerization and cross-linking of collagen and elastin (15). In this context, age-related changes have been observed for protein synthesis and production of ECM components (1,16,17). Further, atomic force microscopy studies indicate that individual epithelial cells show a considerable increase in stiffness in vitro at higher passage numbers (18,19).…”
Section: Introductionmentioning
confidence: 99%